Valuation of Tesla, Inc. - Bílek, Martin (2025)
The main goal of this thesis is to conduct a comprehensive valuation of Tesla, Inc., using three valuation methods: Discounted Cash Flow (DCF), Economic Value Added (EVA), and Relative Valuation. A mixed-method approach combining quantitative financial valuation and qualitative analyses of macroeconomic, industry-specific, and company-specific factors is used. The secondary goal of this thesis is to analyze the relationship between Elon Musk’s tweets and Tesla’s stock price. This is achieved through a combination of sentiment, correlation, and regression analyses. The findings provide a deeper understanding of Tesla’s intrinsic value, as well as the possible reasoning behind its current market price. Moreover, the thesis quantifies the relationship between Elon Musk’s tweeting activity and Tesla’s stock price movements, particularly revealing the possible impact of positive sentiment and higher engagement around the tweets on short-term price increases.